Electroacoustic Analysis of a Controlled Damping Planar CMOS-MEMS Electrodynamic Microphone - TOUNSI, Fares; MEZGHANI, Brahim; RUFER, Libor; MASMOUDI, Mohamed (Archives of Acoustics, 2015)
This paper gives a detailed electroacoustic study of a new generation of monolithic CMOS micromachined electrodynamic microphone, made with standard CMOS technology. The monolithic integration of the mechanical sensor with the electronics using a standard CMOS process is respected in the design, which presents the advantage of being inexpensive while having satisfactory performance. The MEMS microphone structure consists mainly of two planar inductors which occupy separate regions on substrate. One inductor is fixed; the other can exercise out-off plane movement. Firstly, we detail the process flow, which is used to fabricate our monolithic microphone. Subsequently, using the analogy between the three different physical domains, a detailed electro-mechanical-acoustic analogical analysis has been performed in order to model both frequency response and sensitivity of the microphone. Finally, we show that the theoretical microphone sensitivity is maximal for a constant vertical position of the diaphragm relative to the substrate, which means the distance between the outer and the inner inductor. The pressure sensitivity, which is found to be of the order of a few tens of μV/Pa, is flat within a bandwidth from 50 Hz to 5 kHz.